The Anderson's guerrillas and its mission to unify the guerrillas and the USAFFE, 1942-1946 - Calamlam, Juan Paolo M. (2020)
The Anders's guerrillas was among the largest guerrilla units in the Philippines during world war II. Ironically, however, it was among those that seemingly gained less attention in history. By presenting the history of the Anderson's guerrillas, this paper argues that its story and achievements should not be discounted in the study of the resistance movement during the war.
Includes notes (pages 73-82).